Pelatihan Pembuatan Evaluasi Pembelajaran Berbasis Website Edukatif Bagi Guru Madrasah di Al Misbahul Ulum Qur’an Bogor - Widyastuti, Wahyu Tri; Ekowati, Sri Harini; Wahyuningsih, Aida; Vahira, Fara; Taufiq, Salma Fairus (Jurnal Pengabdian UNDIKMA, 2024)
This community service aims to improve the competence of teachers in making educational website-based learning evaluations through the Kahoot and Quizizz applications. The method of implementing this service uses training conducted online and offline with presentation and tutorial techniques. The training was attended by 30 teachers from PAUD, MTs, and MA Madrasah Al Misbahul Ulum Qur'an, Cikereteg, Bogor. This service evaluation instrument uses pre-test and post-test questionnaires which are then analyzed using percentage techniques. The results of this community service activity show that there is an increase in the understanding of madrasah teachers at the Madrasah Al Misbahul Ulum Qur'an, Bogor regarding making educational website-based learning evaluations using the Kahoot and Quizizz applications. In addition, teachers can make learning evaluations using Kahoot and Quizizz for the subjects they teach.